The influence of youngster's satisfaction toward hipster food in kota bharu, Kelantan - Nurdyiana Zambri; Nurhasidah Wahab; Nurnadiah Bahren; Nurul Ain Natasya Amirah Ismail (2022)
Hipster food in Malaysia is a recent invention that has been adapted from diverse concepts, distinctive flavors, and culinary traditions of western nations that are currently popular among young people. Researchers are interested in examining the impact of young people's happiness with hipster food in Kota Bharu, Kelantan because there are an increasing number of hipster eateries or cafes in the area. Young people who have knowledge of and interest in the most recent cuisines served in Kelantan were the subjects of this study. The impact of consumer satisfaction on hipster food restaurant environments, food quality, and service quality is then examined in this research. This study also intends to identify the primary factors influencing the attraction of hipster cuisine among young people in the Kota Bharu, Kelantan area. The researcher will then be able to determine the primary influence of customer satisfaction, particularly among young people, toward hipster food in Kota Bharu, Kelantan, using the study's data at the conclusion of the research. Future research ideas will be presented. Keywords: Youngster’s, satisfaction Hipster food